Basic Level Futsal Referee Training at AFK Pontianak, West Kalimantan - Putra Sastaman B; Y. Touvan Juni Samodra; Maharani Fatima Gandasari; Ghana Firsta Yosika; Isti dwi puspita wati; Eka Supriatna; Uray Gustian; Rubiyatno; Rahmat Putra Perdana; Robby Najini (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
The need for futsal referees in Pontianak is exceptionally high. Futsal activities as a competitive sport require reliable referees, while the number of licensed referees is still limited. Some referees can carry out referee upgrading but find it difficult to carry out activities on their own. This service activity takes the opportunity that the sports coaching education program has a lot of human resources and good cooperative bureaucratic abilities. The collaboration between the study program, the Pontianak futsal association, and the province gave birth to district-level futsal referee upgrading activities. Activities such as event management are carried out by academics consisting of lecturers and students. Activity filters are Referees with licenses as trainers sent by the Provincial futsal association and users. In this case, the Pontianak city futsal association is ready to accommodate and use the results of the activities has been implemented. The result turned out that all the 30 participants who followed were declared passed.